(untitled) (Universal International Scientific Journal, 2026)
This thesis discusses the development of spiritual and psychological stability in preschool children through music therapy. In the thesis, we will present our thoughts on music therapy and its impact on the psychology of preschool children. The thesis analyzes the impact of the family environment and social consciousness on the child’s psyche and shows ways to ensure emotional stability through musical methods. It also discusses the pedagogical and psychological potential of national and world music in the formation of a preschool child’s inner world and the participation of parents in this process.